Minimally Invasive Plate Osteosynthesis (MIPO) in Long Bone Fractures – Biomechanics – Design – Clinical Results - Sirbu, Paul Dan; Petreus, Tudor; Asaftei, Razvan; Berea, Grigore; Botez, Paul (IntechOpen, 2011)
None